Aplikasi Formula Campuran Rizobakteri untuk Pengendalian Penyakit Busuk Akar Rhizoctonia dan Peningkatan Hasil Kedelai di Tanah Ultisol - Andi Khaeruni; Asniah Asniah; Muhammad Taufik; Gusti Ayu Kade Sutariati Ayu Kade Sutariati (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Rhizoctonia root rot disease caused by Rhizoctonia solani is one of the most important disease in soybean area, including at ultisol land in Southeast Sulawesi. Rhizobacteria application is one alternative method to control this pathogen. The aim of this experiment was to study of rhizobacteria indigenous formulation to control of Rhizoctonia root rot disease and increase soybean yield in Ultisol soil. A complete randomized design with seven treatments was used in this experiment. The treatments were (A) rhizobacteria formulation for seed treatment, (B) rhizobacteria formulation for seed treatment and repeated at 2 weeks after planting, (C) rhizobacteria formulation for seed treatment, repeated at 2 and 4 weeks after planting, (D) rhizobacteria formulation for seed treatment and fungicide applied at 2 weeks after planting, (E) fungicide seed treatment, and repeated at 2 weeks after planting, (F) fungicide seed treatment, and repeated at 2 and 4 weeks after planting, and control (without rhizobacteria and fungicides). All treatments were inoculated by R. solani and replicated three times. The results showed that rhizobacteria seed treatment and repeated at 2 and 4 weeks after planting was the most effective treatment to control Rhizoctonia root rot disease, and increase plant height and leaf number up to 119% and 170%, respectively, and increased the yield of soybean up to 1870% in ultisol soil compared to plant with control treatment.